SYNTAX TRANSFORMATIONS OF FOCUS INVERSION IN THE UKRAINIAN TRANSLATION OF THE MAP AND THE TERRITORY BY M. HOUELLEBECQ - Filonenko , Nataliia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article analyzes the peculiarities of translation of narrative sentences with inversion with locative and temporal adverbs, adverbial syntagms or circumstances of time and place in the initial position from the perspective of cognitive perceptual factors reflecting reality in this type of constructions, highlights the logic of on the author’s intention, as well as establishes the patterns of choice of appropriate syntactic construction when translating the sentences with the type of inversion under study. One of the main tasks of the translator is to reproduce the author’s style, in particular when translating the texts of modern popular writers, whose works are translated into many languages. In fiction, French authors use the stylistic potential of certain types of syntactic constructions to convey implicit content. The task of conveying both explicit and implicit meanings in translation determines the use of syntactic constructions that would be equivalent to syntactic constructions of the original text, that is a translational aim to create symmetry of meanings of syntactic units of the original text and translation. Inversion in narrative sentences with adverbial syntagms or circumstances with locative and temporal meanings is often used by modern French authors because of their expressive effectiveness. These constructions are used in the narrator’s speech in order to shift the focus of the reader’s attention to important information for the author and to outline the statics and dynamics of the situation described by the author. A comparison of sentences with focal locative and temporal inversions and the corresponding sentences of the translated text shows that the translator follows the logic of the author of the work and uses the word order that focuses the reader on relevant information. __________ References: • Kovaleva, L. M., Bogdanova, S. Ju., Semenova, T. I. Kognitivnye kategorii v sintaksise [Cognitive categories in syntax] (Irkutsk: IGLU, 2009), 249 (In Russian) • Filonenko, N. G. «Syntaksychna organizacija tekstiv suchasnoi’ francuz’koi’ hudozhn’oi’ prozy: kognityvnyj ta lingvosynergetychnyj aspekty [Syntactic Organisation of the Contemporary French Fictional Prose Texts: Cognitive, Lingual and Synergetic Aspects.» (Dys. d-ra filol. nauk, Kyi’v, 2016), 504 (In Ukrainian). • Fuchs, Fournier,N. «Du rôle cadratif des compléments localisants initiaux selon la position du sujet nominal.» Travaux de linguistique 47 (2003/2): 79-109, https://www.cairn.info/revue-travaux-de-linguistique-2003-2-page-79.htm • Lingvisticae Investigationes, sous la dir 29:1, de K. Gerdes, C. Muller.» (John Benjamins Publishing Company, 2006), 199. • Houellebecq, M. La carte et le territoire (Flammarion, 2010), 427. • Willems, «L’impact de l’ordre des mots sur la prédication: la relation sujet-prédicat.» Travaux de linguistique 26 (1993): 89-101. • Uel’bek, M. Karta i terytorija: roman, per. z fr. L. G. Kononovycha (Harkiv: Folio, 2013 (2012)), 347 (In Ukrainian).